GLOCALIZATION OF INDONESIAN CUISINE IN THE FILM ARUNA DAN LIDAHNYA BY LAKSMI PAMUNTJAK - Ailsa Diah Maharani; Salsabila Hafi; Risma Amalia Citra Dewi; Heny Kurniawati (Vol. 2 No. 1 (2024): Proceeding of International Conference on Cultures & Language 2024, 2024)
Glocalization is the combination of global and local elements in filmmaking. Glocalization also refers to the process of a global phenomenon being adapted to local conditions and values. This effort is to balance between global influences and local interests. The phenomenon of glocalization also has an impact on the existence of local products in the era of globalization. Glocalization can be interpreted as the emergence of a form of interpretation of various global products whose origins are local products carried out by people in various cultural areas. Aruna and Lidahnya is a movie that tells the story of Aruna's culinary journey, a young woman who likes to taste Indonesian regional specialties. This research aims to identify and introduce Indonesia's local culinary diversity. This research shows the process of local culinary adaptation in the face of global influences without losing the original identity. The novelty in this research is to understand and examine the culinary in Indonesia through film using glocalization. The approach in this research uses a qualitative descriptive method. This qualitative descriptive approach is to explore the meanings contained in the film text in depth, as well as to explore the various dimensions of culinary and culture in the film. Data collection was done through listening, recording, and noting relevant elements in the film, such as dialog, scenes, and the context of using social media. The data analysis technique used is an interactive model that includes data collection, data reduction, data presentation to conclusion drawing. The culinary in the film "Aruna & Lidahnya" effectively illustrates the concept of glocalization in the context of Indonesian cuisine by combining local and global elements. So that foreigners or people who are not familiar with Indonesian food know that in the movie Aruna there are foods such as campor larjuk, rujak soto, pengkang. Thus the movie succeeded in raising awareness and appreciation of Indonesian cuisine.